Protective effects of melatonin against 2,3,7,8-tetrachlorodibenzo-p-dioxin-induced cardiac injury in rats - Ediz, Sarihan Mehmet; Hakan, Parlakpinar; Osman, Ciftci; Fethi, Yilmaz; Mustafa, Sagir; Omur, Yilmaz; Gokhan, Ceker (Elsevier, 2015)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is the prototype of a group of highly toxic environmental chemicals. Although there are some suggestions regarding TCDD-induced cardio-toxicity, the exact mechanisms underlying this process have not been fully discovered. One mechanism related to this toxicity is believed to be the generation of reactive oxygen species. Melatonin is known to be a strong antioxidant and has a free radical scavenging ability. Therefore, the aim of this study was to investigate the TCDD-induced cardio-toxicity and the protective effects of melatonin in rats. Rats were randomly divided into 4 equal groups (n = 7 for each group). Group 1 was control; group 2 was TCDD group (2 mu g/kg/week, p.o); group 3 was melatonin group (5 mg/kg/day, i.p.) and group 4 was TCDD and melatonin treatment group. All agents were continued to be administered until the 45th day. Body/heart weights, mean oxygen saturation (PO2%), hemodynamic [mean blood pressure (MBP) and heart rate (HR) from the cannulated-carotid artery] and electrocardiographic evaluations (arrhythmias and duration of PR, QRS and QT intervals), biochemical and histopathological analysis were carried out TCDD exposure caused significant body and heart weight loss, impairment of PO2%, and decrease of MBP and HR levels. Also, major ECG changes and prolongation of PR, QRS and QT durations were observed in TCDD-exposed rats. In biochemical analysis, TCDD significantly induced lipid peroxidation and reduced antioxidant activities. Moreover, our histopathological observations were in accordance with the biochemical results. According to the results, melatonin treatment significantly protected the subjects from TCDD-induced cardio-toxicity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: 2,3,7,8-tetrachlorodibenzo-p-dioxin; Melatonin; Rat; Heart; Wasting syndrome